PENGUATAN KAPABILITAS GURU DALAM MENDESAIN PEMBELAJARAN BERBASIS TPACK DAN PENDEKATAN HEUTAGOGY MELALUI KEMITRAAN MGMP AKUNTANSI DAN KEWIRAUSAHAAN KOTA SEMARANG - Kardiyem, Kardiyem; Astuti, Dwi Puji; Mudrikah , Saringatun; Nuryana, Ita; Khafidz, Abdul; Nasya, Chaila; Larasati, Ratna; Khoirunnisa, Rizki (Universitas Mataram, 2026)
Accounting learning in Vocational High Schools (SMK) still faces challenges in integrating technology with pedagogical approaches that are in accordance with the demands of the 21st century. The problems identified include low teachers' understanding of the concept of Technological Pedagogical Content Knowledge (TPACK) and the heutagogy approach, limited use of digital learning media, and the gap between teachers as digital migrants and Generation Z students as digital natives. Based on the initial survey, only a small percentage of accounting and entrepreneurship teachers in Semarang City implemented TPACK consistently. This service program aims to improve the capabilities of MGMP Accounting and Entrepreneurship teachers in designing TPACK-based learning and heutagogy through the use of AccountingLine media. The activity was carried out on 30 teachers from 12 public and private vocational schools through three stages, namely preparation, implementation of workshops and practical training, as well as monitoring implementation with a community development and education approach. The results of the activity showed an increase in teachers' understanding of TPACK, heutagogy, and the ability to design TPACK-heutagogy-based lesson plans, as well as encouraging motivation to integrate technology in learning. In addition, this program also facilitates the formation of continuous collaboration within the MGMP environment as a forum for sharing good practices of innovative learning.